Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Newton's Law of Gravitation states that the gravitational force between any two objects is the product of their masses divided by the distance between their centres of mass squared all multiplied by the gravitational constant. 
there fore F = (Gm1m2)
Gravitational constant = 6.67x10^-11 ,  F = 1 and m1 and m2 = 2 

apply in above formula we get 1 = (6.67x10^-11 x 2 x 2)/r^2 

rearranging, we get r^2 = 6.67x10^-11 x 2 x 2 

therefore r^2 = 2.6692x10^-10 therefore r = 1.634x10^-5 m 

0 0 0
According to the universal law of gravitation  F=GMm/d^2  whereF=FORCE,G=gravitational const=6.67 x10^-11Nm^2/Kg^2 M and m are the masses and  d is the distance between the two bodies   F=GmM /d^2  d^2=  GMm/F    ie d^2=6.67 x 10^-11  x 2 x  2  /1 =6.67 x4 x 10^-11   =26.68 x10^-11 which is same as 2.668 x10^-10  or d=squre root of2.668 x10^-10 =1.634 x10^-5m 
0 0 0
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts